Impact of Artificial Intelligence on workers - Singh, Jyotsna Amarbahadur; Rawat, Robin Singh (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 4 No 1 (2020): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Artificial Intelligence (AI) is a division of study that hypothesizes, demonstrates and helps advance the potentiality of an electronic device or a computer-controlled machine to think, act and study similar to that of human beings. Completed the past couple of periods, we have observed some major progressions in AI which not only upsurges the scope of the similar but also substitutes the intervention of humans. This swift development of AI has the capability to efficiently disturb the employment sector in the Information Technology field. How to cite this article: Singh JA, Rawat RS.Impact of Artificial Intelligence on Workers. J Adv Res Appl Arti Intel Neural Netw 2020; 4(1): 21-26.